Gut Microbiome-Host Genetics Co-Evolution Shapes Adiposity by Modulating Energy and Lipid Metabolism in Selectively Bred Broiler Chickens - Guangqi Gao; Yangbo Jiao; Lai-Yu Kwok; Zhi Zhong (Animals)
Optimizing fat deposition is crucial for improving chicken production and meat quality. This study investigated the interactive roles of host genetics and gut microbiome in regulating abdominal fat deposition in selectively bred broiler chicken lines. We compared the gut microbiome composition and host whole-genome profiles between fat-line and lean-line broiler chickens that had been selectively bred for divergent abdominal fat levels over 15 generations. Despite identical dietary and environmental conditions, the two chicken lines exhibited significant differences in their gut microbiota. Lean-line broiler chickens exhibited an increased abundance of intestinal Lactobacillus and a decreased presence of potentially pathogenic species, such as Campylobacter coli, Corynebacterium casei, and Enterococcus faecalis. These microbial alterations were accompanied by shifts in the functional metagenome, with enrichment in pathways involved in energy metabolism and nutrient utilization in the lean-line chickens. Notably, the selective breeding process also led to genomic variations in the lean broilers, with single nucleotide polymorphisms predominantly observed in genes related to energy and lipid metabolism. Our findings suggest that the host–microbiome interactions play a key role in the divergent abdominal fat deposition phenotypes observed in these selectively bred chicken lines. The co-evolution of the gut microbiome and host genetics highlights the importance of considering both factors to optimize poultry production efficiency and meat quality. This study offers new insights into the intricate gut–genome interactions in chicken fat metabolism, paving the way for more effective breeding and microbiome-based strategies to manage adiposity in poultry.